Emerging signals of climate change from the equator to the poles: new insights into a warming world - Collins, Matthew; Beverley, Jonathan D.; Bracegirdle, Thomas J.; Catto, Jennifer; McCrystall, Michelle; Dittus, Andrea; Freychet, Nicolas; Grist, Jeremy; Hegerl, Gabriele C.; Holland, Paul R.; Holmes, Caroline; Josey, Simon A.; et al. (Frontiers in Science, 2024)
Human-induced climate change is unequivocally happening now and exerting ever more impacts globally. Access to the latest scientific information on current climate change and projecting future trends is important for planning adaptation measures and for informing international efforts to reduce emissions of greenhouse gases (GHGs). Identification of hazards and risks may be used to assess vulnerability, determine limits to adaptation, and enhance resilience to climate change. This article highlights how recent research programs are continuing to elucidate current processes and advancing projections across major climate systems, and identifies remaining knowledge gaps. Key findings include: projected future increases in monsoon rainfall, resulting from a changing balance between the rainfall-reducing effect of aerosols and rainfall-increasing GHGs; a strengthening of the storm track in the North Atlantic; an increase in the fraction of precipitation that falls as rain at both poles; an increase in the frequency and severity of El Niño Southern Oscillation (ENSO) events, along with changes in ENSO teleconnections to North America and Europe; and an increase in the frequency of hazardous hot-humid extremes. These changes have the potential to increase risks to both human and natural systems. Nevertheless, these risks may be reduced via urgent, science-led adaptation and resilience measures, and by reductions in GHGs.